2013
DOI: 10.1186/1472-6750-13-56
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization applicability of sol–gel matrix immobilized manganese peroxidase produced from an indigenous white rot fungal strain Ganoderma lucidum

Abstract: BackgroundAn eco-friendly treatment of industrial effluents is a major environmental concern of the modern world in the face of stringent environmental legislations. By keeping in mind the extensive industrial applications of ligninolytic enzymes, this study was performed to purify, and immobilize the manganese peroxidase (MnP) produced from an indigenous strain of Ganoderma lucidum. The present study was also focused on investigating the capability of immobilized MnP for decolorization of dye containing texti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…). However, Muhammad Nasir Iqbal and Asgher () reported a higher amount of MnP production (882 ± 13.3 U/mL) by G. lucidum under solid‐state fermentation conditions (moisture, 50%; substrate, 5 g; pH 5.5; temperature, 30C; carbon source, 2% fructose; nitrogen source, 0.02% yeast extract; C : N ratio, 25:1; fungal spore suspension, 5 mL; fermentation time period, 4 days).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…). However, Muhammad Nasir Iqbal and Asgher () reported a higher amount of MnP production (882 ± 13.3 U/mL) by G. lucidum under solid‐state fermentation conditions (moisture, 50%; substrate, 5 g; pH 5.5; temperature, 30C; carbon source, 2% fructose; nitrogen source, 0.02% yeast extract; C : N ratio, 25:1; fungal spore suspension, 5 mL; fermentation time period, 4 days).…”
Section: Resultsmentioning
confidence: 99%
“…). Recently, Muhammad Nasir Iqbal and Asgher () and Lanfermann et al . reported an MnP (48.0 kDa) from G. lucidum and G. applanatum , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iqbal and Asgher immobilized the Ganoderma lucidum strain by the sol-gel matrix entrapment in order to treat different textile effluents. 30 After 4 h of reaction, the industrial effluents were discoloured to a maximum of 99.2 %. Formaldehyde and nitroamines were analyzed in the maximum discoloured effluent and the results showed that the toxicity parameters were below the allowable limits.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of water pollution-related legislation Water Act 1974and Water Cess Act (1977-1988, several restraints are being placed on dye release in industrial wastewaters/effluents because of concerns related to environment and human health. Such legislations have forced industries to remove colouring chemicals from their effluents before they are released into water systems (Iqbal and Asgher, 2013). Several physicochemical methods, such as photocatalysis, ozonation, electrochemical oxidation process, adsorption via activated carbon, coagulation/flocculation, membrane filtration, and precipitation, are usually used for treating textile wastewater but these strategies are expensive and are producing considerable amount of sludge, which has to then be removed safely (Karim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%